"Disrupting peace at home"? Narrating connections between sexual violence perpetrated by armed men and intimate partner violence in (post-)conflict settings. Issue 4 (8th August 2022) - Gray, Harriet; Dolan, Chris
ABSTRACT: While much is now known about the multiple forms of gender-based violence (GBV) to which people are subjected in (post-)conflict spaces, there remains a relative lack of knowledge about how those experiencing such forms of violence perceive the interconnections between them, as well as about how these perceived interconnections are enmeshed in gendered power relations. This article analyzes group interviews carried out with male and female refugees living in Kampala, Uganda, to scrutinize the complex interweaving between GBV and heteropatriarchal gender norms and power relations in (post-)conflict spaces. Participants repeatedly drew causal connections between sexual violence perpetrated by enemy armed men against women and men, and subsequent intimate partner violence. Our discussion of the logics underpinning these perceived causal connections enables close analysis of the shifting and contingent ways in which various forms of GBV are understood as imbricated in one another and implicated in shifting gender norms. This enables us to examine some of the complex ways in which GBV reverberates through gender norms and power relations in (post-)conflict contexts.